Skeletal Muscle Protein Tyrosine Phosphatase 1B Regulates Insulin Sensitivity in African Americans - Stull, April J.; Wang, Zhong Q.; Zhang, Xian H.; Yu, Yongmei; Johnson, William D.; Cefalu, William T. (Diabetes (New York, N.Y.), 2012)
Protein tyrosine phosphatase 1B (PTP1B) is postulated to modulate insulin action by dephosphorylating the insulin receptor signaling proteins and attenuating insulin signaling. We sought to determine the relationship of skeletal muscle PTP1B to whole-body insulin sensitivity. We studied 17 African Americans with type 2 diabetes mellitus (T2DM) and 16 without diabetes. PTP1B gene expression and protein abundance were determined in the biopsied skeletal muscles at the baseline of a hyperinsulinemic-euglycemic clamp. PTP1B gene expression was significantly higher in subjects with T2DM versus control (P < 0.0001) and remained significantly different after adjusting for age and insulin sensitivity (P = 0.05). PTP1B gene expression was positively related to protein abundance (r(s) = 0.39; P = 0.03; adjusted for age and insulin sensitivity) and negatively related to insulin sensitivity (r(s) = -0.52; P = 0.002; adjusted for age). Overexpression and interference RNA of PTP1B were performed in primary human skeletal muscle culture. PTP1B overexpression resulted in reduction of Akt phosphorylation in the control subjects. Moreover, interference RNA transfection downregulated PTP1B expression and enhanced Akt phosphorylation in subjects with T2DM. These data show that skeletal muscle PTP1B gene expression is increased in African American subjects with T2DM, is negatively associated with whole-body insulin sensitivity, and contributes to modulation of insulin signaling.